Refractory kaposiform lymphangiomatosis relieved by splenectomy - Lan, Yuru; Zhou, Jiangyuan; Qiu, Tong; Gong, Xue; Ji, Yi (Frontiers in Pediatrics, 2023)
Kaposiform lymphangiomatosis (KLA) is a rare and complex lymphatic anomaly with a poor prognosis. There is no standard treatment, and drug therapies are the most common therapeutic method. However, some patients' symptoms become gradually aggravated despite medical treatment.Splenectomy may be an alternative option when pharmacological therapies are ineffective. We reviewed and evaluated the cases of 3 patients with KLA who ultimately underwent splenectomy.The lesions were diffusely distributed and involved the lungs and spleens of the 3 patients.Laboratory examinations revealed that all three patients had thrombocytopenia and reduced fibrinogen levels. All patients underwent symptomatic splenectomy after the medication failed. Surprisingly, their symptoms greatly improved. Histopathological investigation of the splenic lesions of the three patients confirmed the diagnosis of KLA. Immunohistochemical staining showed positivity for CD31, CD34, podoplanin, Prox-1 and angiopoietin 2 (Ang-2). This study aimed to review the features of KLA patients treated by splenectomy and explore the underlying link between splenectomy and prognosis. The reason for the improvement after splenectomy may be related to increased Ang-2 levels and platelet activation in patients with KLA. Future research should seek to develop more targeted drugs based on molecular findings, which may give new hope for the treatment of KLA.